Soil chemical composition and texture determinations using neutron-gamma analysis - Aleksandr Kavetskiy; Galina Yakubova; Sidharth Suresh Gautam; Daniel P. Donner; Stephen A. Prior; H. Allen Torbert (Soil and Tillage Research, 2026)

Sediment and runoff losses from rainfall simulation: Effects of elevated atmospheric CO2 and tillage practice - Stephen A. Prior; Dexter B. Watts; G. Brett Runion; Francisco J. Arriaga; H. Allen Torbert (Soil and Tillage Research, 2026)

Long-term response of bahiagrass pastures to elevated atmospheric CO2 and fertility management: Forage quality - Stephen A. Prior; G. Brett Runion; H. Allen Torbert (Soil and Tillage Research, 2025)

Repeated low-dose copper algaecide treatments promote beneficial phytoplankton and zooplankton communities - Michael B. McDonald; Ashley V. Hennessey; Peyton P. Johnson; Matthew F. Gladfelter; Kate L. Merrill; Suzanne E. Tenison; Sathya S. Ganegoda; Tham C. Hoang; H. Allen Torbert; Benjamin H. Beck; Alan E. Wilson (Journal of Environmental Management, 2025)

Measuring and mapping moisture content in agricultural fields by neutron-gamma analysis - Galina Yakubova; Aleksandr Kavetskiy; Stephen A. Prior; H. Allen Torbert (Soil and Tillage Research, 2025)

Evaluating the tolerance of harmful algal bloom communities to copper - Ashley V. Hennessey; Michael B. McDonald; Peyton P. Johnson; Matthew F. Gladfelter; Kate L. Merrill; Suzanne E. Tenison; Sathya S. Ganegoda; Tham C. Hoang; H. Allen Torbert; Benjamin H. Beck; Alan E. Wilson (Environmental Pollution, 2025)

Impacts of flue gas desulfurization (FGD) gypsum on water quality and the algal community in catfish aquaculture ponds - Hannah M. Zinnert; Matthew F. Gladfelter; Suzanne E. Tenison; H. Peyton Poe; Kate L. Merrill; Ashley V. Hennessey; Michael B. McDonald; Dengjun Wang; H. Allen Torbert; Alan E. Wilson (Aquaculture, 2024)

Positive and negative impacts of flue gas desulfurization (FGD) gypsum on water quality - Hannah M. Zinnert; Matthew F. Gladfelter; H. Peyton Poe; Kate L. Merrill; Ashley V. Hennessey; Michael B. McDonald; Dengjun Wang; H. Allen Torbert; Alan E. Wilson (Journal of Environmental Management, 2023)

Effectiveness of flue gas desulfurization gypsum in reducing phosphorus solubility in poultry litter when applied as an in-house amendment - Debolina Chakraborty; Rishi Prasad; Dexter B. Watts; H. Allen Torbert (Waste Management, 2023)

Sorptive removal of phosphorus by flue gas desulfurization gypsum in batch and column systems - Ansley Hamid; Alan E. Wilson; H. Allen Torbert; Dengjun Wang (Chemosphere, 2023)

Nitrogen‐mediated effects of elevated CO 2 on intra‐aggregate soil pore structure - Joshua S. Caplan; Daniel Giménez; Vandana Subroy; Richard J. Heck; Stephen A. Prior; G. Brett Runion; H. Allen Torbert (Global Change Biology, 2017)
Soil pore structure has a strong influence on water retention, and is itself influenced by plant and microbial dynamics such as root proliferation and microbial exudation. Although increased nitrogen (N) availability and elevated atmospheric CO 2 concentrations (eCO 2 ) often have interacting effects on root and microbial dynamics, it is unclear whether these biotic effects can translate into altered soil pore structure and water retention. This study was based on a long‐term experiment (7 yr at the time of sampling) in which a C 4 pasture grass ( Paspalum notatum ) was grown on a sandy loam soil while provided factorial additions of N and CO 2 . Through an analysis of soil aggregate fractal properties supported by 3D microtomographic imagery, we found that N fertilization induced an increase in intra‐aggregate porosity and a simultaneous shift toward greater accumulation of pore space in larger aggregates. These effects were enhanced by eCO 2 and yielded an increase in water retention at pressure potentials near the wilting point of plants. However, eCO 2 alone induced changes in the opposite direction, with larger aggregates containing less pore space than under control conditions, and water retention decreasing accordingly. Results on biotic factors further suggested that organic matter gains or losses induced the observed structural changes. Based on our results, we postulate that the pore structure of many mineral soils could undergo N‐dependent changes as atmospheric CO 2 concentrations rise, having global‐scale implications for water balance, carbon storage, and related rhizosphere functions.

Decomposition of soybean grown under elevated concentrations of CO 2 and O 3 - Fitzgerald L. Booker; Stephen A. Prior; H. Allen Torbert; Edwin L. Fiscus; Walter A. Pursley; Shuijin Hu (Global Change Biology, 2005)
A critical global climate change issue is how increasing concentrations of atmospheric CO 2 and ground‐level O 3 will affect agricultural productivity. This includes effects on decomposition of residues left in the field and availability of mineral nutrients to subsequent crops. To address questions about decomposition processes, a 2‐year experiment was conducted to determine the chemistry and decomposition rate of aboveground residues of soybean ( Glycine max (L.) Merr.) grown under reciprocal combinations of low and high concentrations of CO 2 and O 3 in open‐top field chambers. The CO 2 treatments were ambient (370 μmol mol −1 ) and elevated (714 μmol mol −1 ) levels (daytime 12 h averages). Ozone treatments were charcoal‐filtered air (21 nmol mol −1 ) and nonfiltered air plus 1.5 times ambient O 3 (74 nmol mol −1 ) 12 h day −1 . Elevated CO 2 increased aboveground postharvest residue production by 28–56% while elevated O 3 suppressed it by 15–46%. In combination, inhibitory effects of added O 3 on biomass production were largely negated by elevated CO 2 . Plant residue chemistry was generally unaffected by elevated CO 2 , except for an increase in leaf residue lignin concentration. Leaf residues from the elevated O 3 treatments had lower concentrations of nonstructural carbohydrates, but higher N, fiber, and lignin levels. Chemical composition of petiole, stem, and pod husk residues was only marginally affected by the elevated gas treatments. Treatment effects on plant biomass production, however, influenced the content of chemical constituents on an areal basis. Elevated CO 2 increased the mass per square meter of nonstructural carbohydrates, phenolics, N, cellulose, and lignin by 24–46%. Elevated O 3 decreased the mass per square meter of these constituents by 30–48%, while elevated CO 2 largely ameliorated the added O 3 effect. Carbon mineralization rates of component residues from the elevated gas treatments were not significantly different from the control. However, N immobilization increased in soils containing petiole and stem residues from the elevated CO 2 , O 3 , and combined gas treatments. Mass loss of decomposing leaf residue from the added O 3 and combined gas treatments was 48% less than the control treatment after 20 weeks, while differences in decomposition of petiole, stem, and husk residues among treatments were minor. Decreased decomposition of leaf residues was correlated with lower starch and higher lignin levels. However, leaf residues only comprised about 20% of the total residue biomass assayed so treatment effects on mass loss of total aboveground residues were relatively small. The primary influence of elevated atmospheric CO 2 and O 3 concentrations on decomposition processes is apt to arise from effects on residue mass input, which is increased by elevated CO 2 and suppressed by O 3 .

Elevated atmospheric CO 2 effects on biomass production and soil carbon in conventional and conservation cropping systems - Stephen A. Prior; G. Brett Runion; Hugo H. Rogers; H. Allen Torbert; D. Wayne Reeves (Global Change Biology, 2005)
Increasing atmospheric CO 2 concentration has led to concerns about potential effects on production agriculture as well as agriculture's role in sequestering C. In the fall of 1997, a study was initiated to compare the response of two crop management systems (conventional and conservation) to elevated CO 2 . The study used a split‐plot design replicated three times with two management systems as main plots and two CO 2 levels (ambient=375 μL L −1 and elevated CO 2 =683 μL L −1 ) as split‐plots using open‐top chambers on a Decatur silt loam (clayey, kaolinitic, thermic Rhodic Paleudults). The conventional system was a grain sorghum ( Sorghum bicolor (L.) Moench.) and soybean ( Glycine max (L.) Merr.) rotation with winter fallow and spring tillage practices. In the conservation system, sorghum and soybean were rotated and three cover crops were used (crimson clover ( Trifolium incarnatum L.), sunn hemp ( Crotalaria juncea L.), and wheat ( Triticum aestivum L.)) under no‐tillage practices. The effect of management on soil C and biomass responses over two cropping cycles (4 years) were evaluated. In the conservation system, cover crop residue (clover, sunn hemp, and wheat) was increased by elevated CO 2 , but CO 2 effects on weed residue were variable in the conventional system. Elevated CO 2 had a greater effect on increasing soybean residue as compared with sorghum, and grain yield increases were greater for soybean followed by wheat and sorghum. Differences in sorghum and soybean residue production within the different management systems were small and variable. Cumulative residue inputs were increased by elevated CO 2 and conservation management. Greater inputs resulted in a substantial increase in soil C concentration at the 0–5 cm depth increment in the conservation system under CO 2 ‐enriched conditions. Smaller shifts in soil C were noted at greater depths (5–10 and 15–30 cm) because of management or CO 2 level. Results suggest that with conservation management in an elevated CO 2 environment, greater residue amounts could increase soil C storage as well as increase ground cover.

Elevated Atmospheric CO2 in Agroecosystems: Residue Decomposition in the Field - Stephen A. Prior; H. Allen Torbert; G. Brett Runion; Hugo H. Rogers (Environmental Management, 2004)

Nitrogen and Carbon Cycling in a Model Longleaf Pine Community as Affected by Elevated Atmospheric CO2 - H. Allen Torbert; Stephen A. Prior; G. Brett Runion; Micheal A. Davis; Seth G. Pritchard; Hugo H. Rogers (Environmental Management, 2004)